Resistance switching and formation of a conductive bridge in metal/binary oxide/metal structure for memory devices - Fujiwara, Kohei (2008)
The resistance switching mechanism of a metal/CuO/metal sandwich with a planar device structure has been studied. We report the direct observation of a conducting bridge within the CuO channel of the device, which is formed upon the initial voltage application (forming process). It is found that the resistance switching phenomenon only occurs when just a single bridge is formed during a soft dielectric breakdown. We argue that the reduction and oxidation of this conducting bridge by the action of an applied field and/or current gives rise to a novel nonvolatile memory effect. © 2008 The Japan Society of Applied Physics.